Impact of governance on human development - Zahoor Ahmad; Aysha Saleem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The governance has become a key issue over preceding two decades and it is very important component for good economic growth and human development. If countries want batter growth and human development then good reforms of governance is needed. The main objective of this study is to determine those significant governance indicators that effect the human development. Human development index (HDI) of different countries is taken as dependent variable and six indicators developed by Kaufmann, et al. (1999) to measure the governance named; Political Stability (PS), Voice and Accountability (VA), Regulatory Quality (RQ), Government Effectiveness (GE), Rule of Law (RL) and Control of Corruption (CC) are used as independent variables. Multi-Layer Perceptron (MLP) and Multiple Regression (Stepwise) are used to fulfill the objective. Further predictive ability of the Multiple Regression and MLP is compared. Evidence is provided that Government Effectiveness, Political Stability, Control of Corruption, and Regulatory Quality have significant effect on human development. Further MLP is suggested the most reliable prediction model to predict the HDI.
Keywords: 330; governance; governance indicators; human development; multiple regression and multilayer perceptron